Economic benefits of homestay programme development in selected areas of Selangor, Malaysia - Shahudin, Faizah (2017)
A Malaysian homestay programme is a very unique means to promote authentic cultural heritage experiences and a village (kampung) lifestyle. It generates additional household income by utilising existing natural resources and at the same time providing various economic benefits to the local community. Selangor is one of the prominent states for homestay development in the country, it has registered the highest number of licensed operators and income performance (MOT, 2015). Therefore it is imperative to investigate the economic benefits of the homestay programme, so as to allow quantification of the local finances, expenditure and revenue generation. The main objective of this study is to estimate the economic benefits of visitors’ spending on homestay programme in Selangor to the operators, businesses and communities in the region studied. This study used the Keynesian multiplier method to estimates the output, income and jobs creation in the overall community. The expectation-disconfirmation model was incorporated to evaluate overall visitors’ satisfaction through a comparison of product expectations towards the actual performance of the product using Exploratory Factor Analysis (EFA). A total of 206 questionnaires were distributed to residing homestay visitors, 160 respondents for homestay operators and 200 respondents were from the local community. The major findings from output and employment multipliers have shown significant economic benefits for the entire community. Firstly, the output multiplier figures show that Type I (1.57) and Type II (2.19) indicate a strong connection between magnitude of visitors spending and operators spending towards the overall income and employment benefits. There is practical evidence and implications of these multipliers on income and how homestay programme can be viewed as money spinner to enhance greater potential economic growth. Also, by looking at employment multipliers ratios of 1.12 (Type I) and 1.18 (Type II) it is revealed that employment impact of this programme is highly concentrated on the local people utilisation as a labour. Indeed, the employment and output multipliers from the Selangor homestay programme has shown a bigger impact compared to previous studies done in UK, Great Britain, Perhentian Island, Redang Island and Tioman Island. From EFA and regression analysis, the finding of this study has addressed the significant relationship between visitors’ overall satisfaction subject to destination cultural heritage and motivation to visit. Findings of the study suggest that all of the attributes proposed in the model had significant impacts on the overall visitors’ satisfaction of Selangor’s Homestay. More precisely, homestay programme fostered a better standard of living and healthy lifestyle by improving community socio-economic position. But the future challenge is to develop revenue mechanism to achieve higher income collection and profitability. It was found from this study that the net profit is 29.5%, which can be improved if the operators can retain higher spending from tourist visit. In this context, homestay operator must ensure that the “motivation to visit” and “destination cultural heritage attributes” are managed efficiently to enhance visitors’ satisfaction level. Even though government intervention is needed in policy coordination of events, promotional materials and SME business development, regional planning by all parties involved is essential.